Facile synthesis of cauliflower-like cobalt-doped Ni3Se2 nanostructures as high-performance cathode materials for aqueous zinc-ion batteries. (6th March 2020) - Amaranatha Reddy, D.; Lee, Hwan; Gopannagari, Madhusudana; Praveen Kumar, D.; Kwon, Kiyoung; Yoo, Hyun Deog; Kim, Tae Kyu
Abstract: Ni3 Se2 and Co-doped Ni3 Se2 cauliflower-like nanostructures are synthesized using a simple and feasible electrochemical deposition technique. Electrochemical measurements of the resultant nanostructures in 1 M KOH electrolyte solution revealed that the energy storage performance of the cauliflower-like Ni3 Se2 nanostructures was considerably improved by cobalt doping. Particularly, 6 wt% Co-doped Ni3 Se2 electrodes exhibited remarkable high specific capacity (179.34 mAh g −1 ) and excellent stability with capacity retention of 85.9% over 1000 cycles because of their high electrical conductivity. Furthermore, to verify the feasibility of the optimized Co-doped Ni3 Se2 electrodes for practical applications, Zn ion batteries were constructed by using a Zn plate as the anode and the Co-doped Ni3 Se2 nanostructures as the cathode. The constructed Zn ion battery achieved high energy and power densities of 199.34 W h kg −1 and 24, 510 W kg −1 at the current densities of 1 and 20 A g −1, respectively. In addition, up to 2.2 electrons per formula unit of Ni3 Se2 were successfully utilized, indicating considerably higher utilization of Ni 2+ /Ni 3+ redox sites by Co doping the selenite. This work demonstrated an effectual strategy for rational design of highly robust, low-cost flexible electrodes for energy storage devices. Graphical abstract: We designed a stable and efficient cathode material cauliflower like Co–Ni3 Se2 nanostructures for Zi-ion batteries. The constructed Zn-ion battery achieved high energy and power densities of 199.34 W h kg −1 and 24, 510 W kg −1 at the current densities of 1 and 20 A g −1, respectively. Image 1 Highlights: Co–Ni3 Se2 Nanostructures synthesized by electro chemical deposition technique. Remarkable high specific capacity (179.34 mAh g −1 ) and excellent stability. Achieving high energy and power densities of 199.34 W h kg −1 and 24, 510 W kg −1 . Up to 2.2 electrons per formula unit of Ni3 Se2 were successfully utilized.